1994
DOI: 10.1038/368635a0
|View full text |Cite
|
Sign up to set email alerts
|

Role of guanylyl cyclase and cGMP-dependent protein kinase in long-term potentiation

Abstract: Several lines of evidence suggest that cyclic GMP might be involved in long-term potentiation (LTP) in the hippocampus. Arachidonic acid, nitric oxide and carbon monoxide, three molecules that have been proposed to act as retrograde messengers in LTP, all activate soluble guanylyl cyclase. We report here that an inhibitor of guanylyl cyclase blocks the induction of LTP in the CA1 region of hippocampal slices. Conversely, cGMP analogues produce long-lasting enhancement of the excitatory postsynaptic potential i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

15
253
4
1

Year Published

1996
1996
1998
1998

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 414 publications
(273 citation statements)
references
References 23 publications
15
253
4
1
Order By: Relevance
“…Zaprinast (10 mM), a selective inhibitor of type V (cyclic GMP speci®c) phosphodiesterase (Lugnier et al, 1986), potentiated the relaxant e ects of YC-1 (Figure 1b). Rp-8-Br-cGMPs, a cyclic GMP analogue that inhibits protein kinase G (Zhuo et al, 1994), antagonized the relaxant e ects of YC-1 (Figure 1b). The EC 50 values of YC-1 were 2.9 mM under control conditions, 0.7 mM in the presence of zaprinast (10 mM) and 5.6 mM in the presence of Rp-8-Br-cGMPS (100 mM).…”
Section: E Ects Of Yc-1 On Aortic Tensionmentioning
confidence: 99%
“…Zaprinast (10 mM), a selective inhibitor of type V (cyclic GMP speci®c) phosphodiesterase (Lugnier et al, 1986), potentiated the relaxant e ects of YC-1 (Figure 1b). Rp-8-Br-cGMPs, a cyclic GMP analogue that inhibits protein kinase G (Zhuo et al, 1994), antagonized the relaxant e ects of YC-1 (Figure 1b). The EC 50 values of YC-1 were 2.9 mM under control conditions, 0.7 mM in the presence of zaprinast (10 mM) and 5.6 mM in the presence of Rp-8-Br-cGMPS (100 mM).…”
Section: E Ects Of Yc-1 On Aortic Tensionmentioning
confidence: 99%
“…These studies have largely relied on intracellular application of PKG or make use of the newly developed PKG agonist 8-(pchlorophenylthio)cGMP (8-pCPT-cGMP) or antagonist Rp-8-bromoguanosine 31,5 '-cyclic monophosphothioate, both of which are largely without effects on PDEs or cGMP-gated ion channels. These neuronal effects of PKG include direct roles in regulation of neuronal Ca2~currents (Meriney et al, 1994), control of neuronal firing rates or neurotransmitter release (Woody et al, 1986;Branisteanu et al, 1988;Akamatsu et al, 1993;Pineda et al, 1996), as the presynaptic target for the retrograde messenger in LTP (Zhuo et al, 1994;Arancio et al, 1995), and in the activation of neuronal K~channels (Furukawa et al, 1996). Other direct effects of PKG on cellular function have also been determined in nonneuronal cells that may be of relevance to the brain (for review, see ; also see below).…”
Section: Role Of Pkg In Neurotransmissionmentioning
confidence: 99%
“…LTP in chick ciliary ganglia is mimicked by cGMP analogues at the initiation or maintenance phase of LTP (Lin and Bennett, 1994). Zhuo et al (1994) have shown that a GC inhibitor blocks the induction of LTP in the CAl region of hippocampal slices. Conversely, cGMP analogues produce long-lasting enhancement of the excitatory postsynaptic potential, associated with an increase in PKG activity.…”
Section: Ltp and Long-term Depression (Ltd)mentioning
confidence: 99%
See 1 more Smart Citation
“…However, despite the fact that the NO-coupled cyclic GMP pathway has a widespread anatomical distribution in the mammalian brain (Bredt et al, 1990;Förstermann et al, 1990;Furuyama et al, 1993;Burgunder and Cheung, 1994), its functions are not well understood. One hypothesized function is the modulation of synaptic strength, 1651 both in the immature brain, when developmental programs specify the survival and elimination of specific synapses Wu et al, 1994;Ogilvie et al, 1995;Wallhausser-Franke et al, 1995;Wang et al, 1995;Wetts et al, 1995;lentile et al, 1996), and in the mature brain, when certain types of neural activity induce long-term (Daniel et al, 1993;Hartell, 1994;Zhuo et al, 1994;Arancio et al, 1995;Boulton et al, 1995;Boxall and Garthwaite, 1996) or transient (Boulton et al, 1994;Broome et al, 1994) changes in synaptic efficacy.…”
mentioning
confidence: 99%